2021
DOI: 10.1111/apt.16527
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: natural history of hepatitis delta virus‐induced liver disease ‐ less severe today but still needs attention

Abstract: LINKED CONTENT This article is linked to Palom et al paper. To view this article, visit https://doi.org/10.1111/apt.16485

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…31 The reasons for less active disease in our CHD cohort may be past interferon treatment-induced partial viral response 32,33 or recent descriptions of less severe disease, 34,35 possibly as a consequence of a slower turnover of HDV in the community compared to the past. 34,36 The best performance in correctly identifying cirrhosis was obtained with TE which displayed an excellent AUROC of 0.945 for the determination of cirrhosis similar to data reported by Da et al 5 These data are also in congruent with data reported for CHB and CHC. [37][38][39] At a cut-off of 10 kPa, TE predicted cirrhosis with a sensitivity of 95% and specificity of 75%.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…31 The reasons for less active disease in our CHD cohort may be past interferon treatment-induced partial viral response 32,33 or recent descriptions of less severe disease, 34,35 possibly as a consequence of a slower turnover of HDV in the community compared to the past. 34,36 The best performance in correctly identifying cirrhosis was obtained with TE which displayed an excellent AUROC of 0.945 for the determination of cirrhosis similar to data reported by Da et al 5 These data are also in congruent with data reported for CHB and CHC. [37][38][39] At a cut-off of 10 kPa, TE predicted cirrhosis with a sensitivity of 95% and specificity of 75%.…”
Section: Discussionsupporting
confidence: 83%
“…Similar data were reported from our group a decade earlier 31 . The reasons for less active disease in our CHD cohort may be past interferon treatment‐induced partial viral response 32,33 or recent descriptions of less severe disease, 34,35 possibly as a consequence of a slower turnover of HDV in the community compared to the past 34,36 …”
Section: Discussionsupporting
confidence: 82%
“…Even in small-scale studies performed in tertiary centers, there appears to be little effort to differentiate between these two conditions, which may be attributed to a lack of non-invasive instruments, such as the routine use of quantitative HBsAg measurements or the lack of wide-spread availability of transient elastography. On the other hand, it may also suggest that milder forms of chronic HDV may be increasing [21] , [22] , [23] , [24] . The lack of a robust and cheap biomarker availability at every clinical setting to differentiate HBeAg-negative CHB infection from HBeAg-negative (non-cirrhotic) CHB is likely one reason why there is significant heterogeneity between outpatient studies.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, HDV infection has been associated with a milder course than in the past, when fulminant hepatitis and rapid progression to cirrhosis was more commonly reported; this was most likely due to more pathogenic emerging strains of HDV rapidly circulating among HBeAg-positive subjects. 70 Acute hepatitis can be either monophasic or biphasic depending on the relative titres of the two viruses, the first peak usually being caused by HBV and the second by HDV. 64 In the setting of a super-infection, HDV takes advantage of the pre-existing HBsAg and immediately establishes infection.…”
Section: Natural Historymentioning
confidence: 99%